The pricing dynamics of cross-listed securities: The case of Chinese A- and H-shares - Cai, Charlie X.; McGuinness, Paul B.; Zhang, Qi (Journal of Banking & Finance, 2011)
We develop a non-linear Markov error correction approach to examine the general co-integration relation between the H- and A-prices of cross-listed Chinese stock issuers across the period January 1999 to March 2009. We unravel three important dimensions of this relation. These pertain to (i) the long-run expectation of the H- (to A-price) discount; (ii) the level of short-run co-movement in prices; and (iii) the magnitude of error corrections. Findings point to significant improvements in all three areas. Policy and corporate governance change appears to be the principal force driving the efficiency gains. Weakening informational asymmetries underlie much of the change in the markets’ relative pricing. In contrast, sentiment effects strongly underpin the contemporaneous response and error correction adjustments. Finally, the escalating Global Financial Crisis of 2008 appears to have not only bolstered the A- and H-markets’ short-term pricing dynamic but also temporarily increased the long-term H-share discount.